1992
DOI: 10.1172/jci116086
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight iron and the oxygen paradox in isolated rat hearts.

Abstract: Little is known about changes in the amount of iron in the intracellular low molecular weight pool, which catalyzes the Fenton reactions during reperfusion after ischemia. In this study a new approach is presented to measure low molecular weight iron and it is applied to normal hearts during ischemia and to iron-loaded hearts during anoxia and reoxygenation. The results of this study show that (a) during ischemia in normal hearts a progressive 30-fold increase occurs in low molecular weight iron after 45 min o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 30 publications
1
52
1
Order By: Relevance
“…Therefore, the toxic effect of myocardial iron is dynamic and is increased in the presence of metabolic acidosis. 40 Based on the available data, it is logical to assume that peri-infarct ischemic myocardium, the target for SPIO-mediated stem cell therapy, is particularly susceptible to iron toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the toxic effect of myocardial iron is dynamic and is increased in the presence of metabolic acidosis. 40 Based on the available data, it is logical to assume that peri-infarct ischemic myocardium, the target for SPIO-mediated stem cell therapy, is particularly susceptible to iron toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although acute ischemia results in a spike in circulating and tissue catalytic iron, this does not appear to be solely a marker, but also a causal agent of worsened injury. Improved recovery of myocardial function after ischemia has been demonstrated with iron chelation (eg, deferoxamine) in animal models 10,16 and in one human study, providing indirect support for the toxicity of catalytic iron. Paraskevaidis et al suggested deferoxamine infusion was able to reduce myocardial stunning following elective coronary artery bypass grafting and improve long-term ejection fraction.…”
Section: Iron In Cardiovascular Diseasementioning
confidence: 98%
“…Abbreviations: CHF, congestive heart failure; CrCl, creatinine clearance; CV, cardiovascular; DM, diabetes mellitus; HR, hazard ratio; NT-pro-B-type natriuretic peptide, N terminal pro-B-type natriuretic peptide; MI, myocardial infarction. myocardium 10,16 and kidney. 17 In a rat model, Voogd et al demonstrated significant increases in the low-molecularweight-iron content of cardiac tissue after ischemia; similar results were found in a kidney model of ischemia.…”
Section: Iron In Cardiovascular Diseasementioning
confidence: 99%
“…Iron within the liver is found in several biochemical forms such as ferritin, hemosiderin, heme, and also in the putative intracellular low molecular weight form chelated to nucleotides, amino acids and other low molecular weight compounds (8)(9)(10). Various theories of cellular toxicity resulting from excess iron deposition emphasize specific cytopathologic mechanisms whereby chronic iron overload causes organelle damage and altered cell function (4,11).…”
Section: Introductionmentioning
confidence: 99%